INTERNAL OR EXTERNAL? FACTORS INFLUENCE ACCEPTANCE OF KNOWLEDGE ABOUT RIVER FUNCTIONS IN JELAWAT PARK VISITORS: Array - Rahman, B.; Kautsary, J. (Municipal economy of cities. Series: «Economy science», 2022)
River border development is a problem in almost all cities. Previous research has discussed river border development from environmental, economic, legal, and socio-cultural aspects. This research is entered to fill the gap from the educational aspect, reviewing its influence as a potential media for river conservation to provide recommendations from problems to potential. This paper investigates the determinants that influence the level of knowledge of visitors to Taman Jelawat as a river border park on the function of the Mentaya River. Using logistic regression, the study sample consisted of 150 visitors to Taman Jelawat. The results showed that the distance from the visitor’s residence to the river was an internal factor influencing the level of knowledge of river functions. While the external factors of visitors or factors from Jelawat Park became dominant with repeated visits, friends visiting, and favorite park zones as factors that could significantly influence the level of knowledge of Jelawat Park visitors. This shows that Jelawat Park as a river order park can be a good meeting point for humans and rivers. Meeting points can be useful for preserving river functions by building community knowledge about river functions.